New approaches in personnel selection - Atalaya Pisco, María (2001)
The article tries on the new focuses of the selection process of personal, which highlight to the personnel of the organizations like the most valuable asset and its importance for the success and I execute of the objectives of the company. Also, it analyses the characteristics of the agile organizations as an emergent model of company with great easiness of adapting to the change and it describes the profile of the worker of the future.